Bagaimana cara memilah dokumen rekam medis aktif dan tidak aktif?: Efisiensi penggunaan Ms. Access 2016 di Puskesmas Dinoyo - Ervita Nindy Oktoriani; Sukron Jazuli; Suhartina ina Ina; Basirun Sirebut (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
The medical record document sorting system is now developed using information technology. One of the software that can be utilized in the process of selecting medical record documents is Microsoft Access 2016. In the medical record unit, Dinoyo Public Health Center still uses manual recording especially for the retention of active and inactive medical record documents. Therefore the author’s took the initiative to make a medical record application based on Ms. Access 2016. To that end, this study was conducted to see the efficiency of the application of this medical record application at Dinoyo Public Health Center. This type of research is a qualitative research with a descriptive approach, because author’s want to describe the application of Ms. based medical record applications, Access 2016. The instruments used were observation sheets, closed questionnaires, and brief interview guidelines. In addition, author tabulated simple statistical data to sharpen research results. Based on the results of the study, there was enhance in efficiency in the performance of officers in sorting active and inactive medical records documents. This increase shows that the use of the medical record application can improve the efficiency of sorting active and inactive medical record documents at Dinoyo Public Health Center